Applying an organizational effectiveness approach to measure family business performance. Issue 3 (23rd May 2019) - Williams Jr, Ralph I.; Pieper, Torsten; Kellermanns, Franz; Astrachan, Joe
Abstract : Purpose: Current approaches to measuring family business performance have limitations: failing to acknowledge the entire family business holistically, and lacking recognition of the idiosyncratic nature of family business goals. By applying organizational effectiveness and the achievement of desired organizational outcomes, the purpose of this paper is to develop a scale to measure performance based on a family business' idiosyncratic goals. Design/methodology/approach: This study applies mixed methods, including qualitative research, two surveys and structural equation modeling. Findings: The authors develop a scale employing 21 items, representing six goal dimensions, to measure the family business performance. Originality/value: The family business performance measurement scale from this study responds to multiple calls for a scale gauging family business performance in a manner including both financial and non-financial outcomes.